Efficiency of Islamic banks in Malaysia: a comparison between local Islamic banks and foreign Islamic banks - Mohamad Syahir, Ab Halim (2019)
This research paper study the on efficiency level for all Islamic banks in Malaysia during the year 2008 to 2016.Other than that, this research paper compare the efficiency of the local Islamic banks and foreign Islamic bank in Malaysia during the same period of the study. The efficiency of all Islamic in Malaysia is measured by utilizing Data Envelopment Analysis. The data are extracted by Bank scope and Annual Report from 2008 to 2016. The samples consisted of 16 Islamic banks in Malaysia. In overall, the finding shows that Islamic banks in Malaysia perform efficiently. Other than that, the finding shows that local Islamic banks more efficient compare to foreign Islamic banks. Hence, the findings of this research have policy implications and make a contribution to policy-making by providing empirical evidence on the performance of the Islamic banks and their efficiency level.